Strategi Penerimaan Murid Baru Berbasis Asesmen Daerah di Kota Yogyakarta - Sri Lestari Andayani; Nerys Lourensius (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to analyze the regional assessment-based student admission strategy in Yogyakarta City, addressing the issues of unequal selection tools and unequal school distribution. The use of report card scores as a selection tool often does not consistently reflect student abilities across schools, while uneven distance zoning due to existing city design since the colonial era worsens the distribution of educational access. Some areas in Yogyakarta even become